A note on a generalization of a statistical matrix. Issue 12 (18th June 2021) - Farhadian, Reza
Abstract: A generalization of the well-known Helmert matrix was recently introduced in [Akkus, I., and G. Kizilaslan. 2019. Generalization of a statistical matrix and its factorization. Communications in Statistics - Theory and Methods . doi:10.1080/03610926.2019.1645854.]. We consider a modified form of this generalization and we obtain the LU decomposition (in closed form) of this modified generalized matrix. We also prove some special cases, that are all orthogonal, only using the Helmert matrix.